The Analysis Of Students’ Motivation In Learning English (A Case Study Inside Classroom) Of The Eleventh Grade Students Of SMKS Taman Madya Baiturrahman Bima 2018 - Annisah; Waliyudin; Julia Anggraini (STKIP Taman Siswa Bima, 2018)
The thesis is written aimed to know how are the students’ motivations in learning English (a case study inside classroom) of the eleventh grade students of SMKS Taman Madya Baiturrahman Bima in academic year 2017/2018. This research was descriptive research. The subjects of this research were the students of Computer Program (TKJ) of eleventh grade in SMKS Taman Madya Baiturrahman Bima. To collect the data, the researchers used questionnaire that has been made based on criteria and condition of students. The researchers also used video recording to support the questionnaire data. The result of the data analysis, there are two important kinds of motivation in this research, based on 4 criteria and condition of questionnaire were internal and external motivation. In internal motivation, the researchers was taken 61,9% the high percentage of students have good attention in positive statements and more than 38,0% students attention in negative statements. In external motivation, the percentage of positive statements was 61,9% students and more than 28,5% students in negative statements. That’s mean the students’ motivation in Learning English (a case study inside classroom) of the eleventh grade students of SMKS Taman Madya Baiturrahman Bima in academic year 2017/2018 stay in a middle were the researchers took the high percentage of internal and external motivation in positive statements was 61,9% students.